MATRIX METALLOPROTEINASE-3 LEVELS IN RHEUMATOID ARTHRITIS AND ITS RELATIONSHIP WITH OTHER DISEASES - Tuncer, T.; Kaya, A.; Gulkesen, A.; Kal, G. A.; Akgol, G. (Bmj Publishing Group, 2015)
[Abstract Not Available]